2020
DOI: 10.1002/jeab.599
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and maintenance of delayed matching‐to‐sample in tufted capuchin monkeys

Abstract: Delayed matching-to-sample (DMTS) is a commonly used procedure to investigate short-term memory. For the study of functions of forgetting, the delay between the disappearance of the sample stimulus and appearance of choices is manipulated. The intertrial interval (ITI) is also varied to assess interference effects. Performance decrements have been observed as delay increases and, in some cases, performance recovery occurs when ITIs are increased. Other studies indicate that the higher the ITI/delay ratio, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Roberts and Kraemer (1982, 1984) varied ITI in a delayed matching‐to‐sample task and found that accuracy increased monotonically with ITI (as did Colares Leal et al, 2020). The logarithm of the ITI/delay ratio provided a near‐perfect prediction of accuracy for their data.…”
Section: Classic Schedulesmentioning
confidence: 89%
See 1 more Smart Citation
“…Roberts and Kraemer (1982, 1984) varied ITI in a delayed matching‐to‐sample task and found that accuracy increased monotonically with ITI (as did Colares Leal et al, 2020). The logarithm of the ITI/delay ratio provided a near‐perfect prediction of accuracy for their data.…”
Section: Classic Schedulesmentioning
confidence: 89%
“…A short ITI moved the prior reinforcer closer to the next feeding, enhanced its directive strength, and thus slowed acquisition of sign tracking to the CS. Kraemer (1982, 1984) varied ITI in a delayed matching-to-sample task and found that accuracy increased monotonically with ITI (as did Colares Leal et al, 2020). The logarithm of the ITI/delay ratio provided a near-perfect prediction of accuracy for their data.…”
Section: Cue Competition Elsewherementioning
confidence: 99%
“…If subjects are sensitive to pressure, their performance should be different on trials with the high-pressure cues than on low-pressure trials, despite the identical difficulty level between the two types of trials. Given human differences in propensity to choke or thrive and capuchins’ individual differences on working memory tasks 15 , 24 , we predicted the existence of individual differences in how capuchins responded to high pressure trials. To assess the relationship between individual differences in naturally-occurring cortisol and a given monkey’s change in performance between trial types, we concurrently collected fecal samples throughout the testing period.…”
Section: Introductionmentioning
confidence: 99%